Rebel Yell: Exploring Gender Resistance in Women’s Punk Subculture - Pardamean Daulay; Muta’allim; Hasan Sayfullah; Alifathur Rohmah; Hafni Hafsah (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
The female punk subculture highlights resistance to dominant gender norms. This study explores gender resistance within the female punk subculture through the lenses of culture, identity, and activism. In the punk movement, women are often placed in peripheral positions. However, this research shows that this subculture becomes an important space for active resistance against sexism and patriarchy. This study is a descriptive qualitative research with a gender performativity approach. The study focuses on the female punk movements in Ujung Berung, Bandung, using participant observation, recording techniques, and interviews with various stakeholders including community leaders and local residents. The researcher observed the resistance and movements of female punks through recording and noting techniques. Additionally, the researcher conducted interviews with female punks, community leaders, and local residents. After the data was collected, the researcher performed data reduction, classification, validation, and coding in tables, followed by interpretation. The research findings indicate three main roles in gender resistance within the punk subculture, they were the role of women in the punk subculture; the expression of identity and gender resistance; and the impact of women's movements within the punk subculture